Features of excitation of the hydrogen (deuterium)-metal system by an electron bunch; Technical Physics; Vol. 56, № 1 - Tyurin Yu. I. Yuri Ivanovich; Larionov V. V. Vitaliy Vasilyevich; Chernov I. P. Ivan Petrovich; Sklyarova E. A. (2011, 2011)
We report on the results of mass-spectroscopic analysis of the hydrogen yield from metals saturated with hydrogen under the action of accelerated electrons (with an energy of up to 100 keV and a current density from 3 to 30 μA). It is found that the desorption rate is determined not only by parameters of the electron bunch, but also by the structure of the oxide film. It is discovered that the electronic subsystem of hydrogen-enriched metals enhances their ability to absorb the energy of the external electromagnetic action and to preserve it for a longer time as compared to a pure metal. This facilitates nonequilibrium migration and yield of hydrogen under the action of radiation in the subthreshold range. A theoretical model is proposed and analytic dependences are derived for the intensity of hydrogen yield from metals exposed to an electron bunch. The results of this study can be used for the removal of hydrogen from metals and for obtaining submicrocrystalline materials (e.g., titanium).